Significant improvement of glycemic control in diabetic patients with HCV infection responding to direct‐acting antiviral agents. Issue 2 (14th November 2017) - Ciancio, Alessia; Bosio, Roberta; Bo, Simona; Pellegrini, Marianna; Sacco, Marco; Vogliotti, Edoardo; Fassio, Giulia; Bianco Mauthe Degerfeld, Andrea G. F.; Gallo, Monica; Giordanino, Chiara; Terzi di Bergamo, Lodovico; Ribaldone, Davide; et al.
Abstract : Many studies showed insulin resistance amelioration in HCV‐patients achieving Sustained Virologic Response (SVR) but results on glycemic control in diabetic patients are unclear. This study aimed to assess fasting glucose (FG) and glycated hemoglobin (HbA1c) values before and after therapy with direct‐acting antivirals (DAAs) in HCV‐patients with type 2 diabetes mellitus (T2DM). Of the 122 consecutively recruited patients with chronic hepatitis C and T2DM, 110 patients were treated with DAAs and 12 remained untreated. Clinical, biochemical, virological, and metabolic features were collected both at baseline and at 12 weeks after the end of therapy (EOT) or after a comparable period of time in untreated patients. A total of 101 patients obtained a SVR (Group 1), while nine were relapsers. Group 2 (21 patients) was composed by the nine relapsers and the 12 untreated patients. A significant reduction of mean FG (134.3 ± 41.32 mg/dL vs 152.4 ± 56.40 mg/dL, P  = 0.002) and HbA1c values (46.51 ± 16.15 mmoL/moL vs 52.15 ± 15.43 mmoL/moL, P  <  0.001) was found in Group 1 but not in Group 2 (140.6 ± 47.87 mg/dL vs. 145.31 ± 30.18 mg/dL, P  = 0.707, and 55.31 ± 20.58 mmoL/moL vs. 53.38 ± 9.49 mmoL/moL, P  = 0.780). In Group 1, 20.7% of patients could reduce or suspend their antidiabetic therapy compared to none in Group 2 ( P  = 0.03), despite the significant weight increase observed in Group 1. SVR induced a significant amelioration of glycemic control in diabetic HCV‐patients, despite a significant weight increase; larger prospective studies are needed to verify whether these results are maintained over the long‐term.